INFLUENCE OF LEADERSHIP, WORK MOTIVATION AND COMPENSATION ON EMPLOYEE PERFORMANCE - Faisal Rahman Dongoran; Dedy Husrizal Syah (International Journal of Economic, Technology and Social Sciences (Injects), 2020)
Performance is very important for a company, because employee performance is a benchmark for companies to assess capabilities, productivity and provide useful information for matters related to employees. This research is based on the not maximum employee performance at PT Pos Indonesia (Persero) Medan. The type of research in this study is associative. The population in this study is an employee of PT. Pos Indonesia I (Persero) Medan and for samples taken as many as 78 people. The data collection techniques in this study list questions. The results showed that simultaneously leadership, Work Motivation and compensation were positively and significantly impacted the employee  performance. Partially, leadership, Work Motivation and compensation  were also positively and significantly impacted the employee  performance of  POS Indonesia Company Medan.